Pengaruh Pendapatan Asli Daerah, Dana Alokasi Umum, Dana Alokasi Khusus dan Dana Bagi Hasil terhadap Belanja Modal: Studi Kasus Badan Pengelola Keuangan dan Aset Daerah Provinsi Aceh - Wahyu Haji Muharram; Andri Soemitra; Nurwani Nurwani (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2025)
This research is motivated by several factors such as locally generated revenue, general allocation funds, special allocation funds, revenue-sharing funds, and capital expenditure. Some of the problems identified in this study include the realization of locally generated revenue that has never reached the budget target over four consecutive years, a percentage decrease in locally generated revenue while capital expenditure remains constant, and the absence of certain special allocation funds, which may affect capital expenditure. The purpose of this study is to determine the effect of locally generated revenue, general allocation funds, special allocation funds, and revenue-sharing funds on capital expenditure. This research employs a descriptive quantitative method using data samples obtained from the Regional Financial and Asset Management Agency of Aceh Province in the form of Budget Realization Reports for the period 2019–2022. The data analysis technique used is linear regression. The results show that, based on the simultaneous test (F-test), locally generated revenue, general allocation funds, special allocation funds, and revenue-sharing funds have a positive and significant effect on capital expenditure. Meanwhile, based on the partial test (t-test), each of these variables—locally generated revenue, general allocation funds, special allocation funds, and revenue-sharing funds—also has a positive and significant effect on capital expenditure.